Nereididae (Annelida: Phyllodocida) of the Persian Gulf and Gulf of Oman, including description of two new species and 11 new records - Bonyadi-Naeini, Alieh; Rastegar-Pouyani, Nasrullah; Rastegar-Pouyani, Eskandar; Glasby, Christopher J.; Rahimian, Hassan (Zootaxa, 2017)
Currently, only 31 nereidid species are known from the Persian Gulf and Gulf of Oman. The present study was carried out in order to investigate the poorly known diversity of nereidid polychaetes from seas of the southern coasts of Iran. Specimens were collected from 23 locations along the intertidal zones of the two water bodies. Among the 26 species found: two are new, and are described here, including Simplisetia qeshmensis sp. nov. and Neanthes biparagnatha sp. nov.; 11 are new geographical records. Neanthes biparagnatha sp. nov. is most similar to N. deplanata (Mohammed, 1971), which is also found in the Persian Gulf, but can be most easily distinguished from it by the presence of bars in addition to cones in Area IV of the pharynx. Simplisetia qeshmensis sp. nov. may be distinguished from its closest congener, S. erythraeensis (Fauvel, 1918), also reported from the Persian Gulf, by having a greater number of paragnaths in Area I of the pharynx, an additional type of chaeta (homogomph spinigers) in the ventral neuropodial fascicle and having a reduced notopodial lobe in posterior chaetigers. The list of new records includes: one species from both areas, Neanthes glandicincta (Southern, 1921); eight species from the Persian Gulf, Leonnates decipiens Fauvel, 1929, Neanthes acuminata (Ehlers, 1868), Neanthes sp., Neanthes sp. cf. N. acuminata, Nereis sp. cf. N. pelagica Linnaeus, 1758, Perinereis cultrifera (Grube, 1840) species complex., Pseudonereis trimaculata (Horst, 1924), Pseudonereis sp. cf. P. variegata (Grube, 1857) and two from the Gulf of Oman, Leonnates persicus Wesenberg-Lund, 1949 and Perinereis kuwaitensis Mohammed, 1970. The present study brings to 40 the number of nereidid species currently known from the Persian Gulf and Gulf of Oman. A taxonomic key to nereidid species from the intertidal zones of the Persian Gulf and Gulf of Oman is presented to facilitate future investigations.